PENGARUH SERVICE EXCELLENCE DAN HARGA TERHADAP LOYALITAS PELANGGAN PADA AZWA PERFUME PEKANBARU - Novri Yanti; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is conducted at Azwa Perfume Pekanbaru which is located at Teuku Umar Street No 79, Rintis, Lima Puluh, Pekanbaru. The purpose of this research is to know how big influence of service excellence and price to consumer loyalty at Azwa Perfume Pekanbaru. Samples in this study were taken as many as 100 respondents and the techniques used accidental sampling. The data in this study using survey method through questionnaires filled by consumers. The data obtained from the questionnaire and then processed to then tested through statistics through the SPSS program.Hypothesis testing using simple linear analysis method and multiple linear analysis. From the results of tests conducted indicate that service excellence and price have a positive and significant impact on consumer loyalty in Azwa Perfume Pekanbaru. With R2 value of 0.700. This shows that service excellence and price give 70% influence on consumer loyalty at Azwa Perfume Pekanbaru, while the remaining 30% influenced by other variables not examined in this study.Keywords: Service Excellence, Price and Consumer Loyalty